Squamous Cell Papilloma of the Esophagus: A Case Series Highlighting Endoscopic and Histologic Features. (2nd June 2020) - Uhlenhopp, Dustin J.; Olson, Kristin M.; Sunkara, Tagore
Abstract : Esophageal squamous papillomas are rare epithelial lesions typically discovered incidentally during EGD. Their prevalence is estimated to be less than 0.01% in the general population. We present three cases of esophageal squamous papillomas identified histologically. It may be possible to identify these lesions macroscopically. One study provided a positive predictive value of 88% for squamous papilloma utilizing the triad of exophytic growth, wart-like projections, and surface vessel crossing seen on narrow band imaging during endoscopy. The etiology is unclear. Chronic mucosal irritation from GERD or esophagitis is the prevailing theory of pathogenesis, but HPV has been detected in some lesions. The malignant potential of these lesions is considered controversial. There are documented cases demonstrating complications with squamous cell carcinoma, so we recommend removal of all esophageal squamous papillomas; however, the small absolute number of cases documented in the literature makes drawing any associations or conclusions between esophageal squamous papillomas and squamous cell carcinoma difficult. Further research is needed regarding treatment and surveillance. This case series helps contribute to the small but growing literature of this rare finding.